Population dynamics and antimicrobial resistance of Salmonella Derby ST40 from Shenzhen, China - Miaomiao Luo; Yiying She; Yixiang Jiang; Li Xie; Chao Yang; Yaqun Qiu; Rui Cai; Yinghui Li; Liangcai Xu; Lulu Hu; Lei Wang; Shuang Wu; et al. (Frontiers in Microbiology, 2022)
Salmonella enterica subsp. enterica serovar Derby (S. Derby) is one of the most common serotypes responsible for salmonellosis in humans and animals. The two main sequence types (ST) observed in China are ST40 and ST71, with ST40 presently being the most common in Shenzhen. Recent years have seen an increasing number of cases of salmonella caused by ST40 S. Derby, but the epidemiology is not clear. We gathered 314 ST40 S. Derby isolates from food and patient samples for 11 years in Shenzhen; 76 globally prevalent representative strains were also collected. Whole-genome sequencing (WGS) combined with drug resistance phenotyping was used to examine population structural changes, inter-host associations, drug resistance characteristics, and the food-transmission risks of ST40 S. Derby in Shenzhen over this period. The S. enterica evolutionary tree is divided into five clades, and the strains isolated in Shenzhen were primarily concentrated in Clades 2, 4, and 5, and thus more closely related to strains from Asian (Thailand and Vietnam) than European countries. Our 11-year surveillance of S. Derby in Shenzhen showed that Clades 2, 4, and 5 are now the dominant epidemic branches, and branches 2 and 5 are heavily multi-drug resistant. The main resistance pattern is ampicillin-tetracycline-ciprofloxacin-chloramphenicol-nalidixic acid-streptomycin-sulfamethoxazole/trimethoprim. This may lead to a trend of increasing resistance to ST40 S. Derby in Shenzhen. Using a segmentation of ≤3 SNP among clone clusters, we discovered that Clades 2 and 4 contained multiple clonal clusters of both human- and food-derived strains. The food-derived strains were mainly isolated from pig liver, suggesting this food has a high risk of causing disease outbreaks in Shenzhen.